Most Valuable Player Algorithm Based State Estimation for Energy Systems - Shanmugapriya, S.; Maharajan, D. (Distributed Generation & Alternative Energy Journal, 2021)
State estimation (SE) processes the real-time measurements and provides database to energy control centre for safety control of energy systems. Tradi- tionally Weighted Least Square (WLS) and Weighted Least Absolute Value (WLAV) based algorithms have been suggested for SE but the development of very fast computers and parallel processing enable the system engineers to think of employing the computationally inefficient evolutionary algorithms, which are known to be robust and stable, in solving SE problems. This paper suggests a most valuable player algorithm based SE involving WLS and WLAV objectives one at a time, and presents results on four IEEE test systems for illustrating its superiority.